2019
DOI: 10.12688/f1000research.18095.4
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of the utilization of durian peel liquid smoke as a natural preservative for mackerel

Abstract: Background: Durian peel is a type of biomass waste that contains cellulose, hemicelluloses, and lignin. The pyrolysis of these compounds results in production of liquid smoke which can be used as a natural preservative to replace current synthetic preservatives. This research assessed the ability of liquid smoke produced during pyrolysis of durian peel to preserve fish. Methods: Dry durian peel waste underwent batch reactor pyrolysis at 340°C and 380°C, resulting in production of liquid smoke (grade 3), charco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…Smoke condensates are usually obtained from wood smoke produced by smoldering wood chips or sawdust followed by refining and rinsing steps to remove unwanted compounds (Guillén et al., 2000; Montazeri, Oliveira, et al., 2013). Despite the filtering, the active antimicrobial compounds are still the same and research has shown an inhibiting effect of several types of PCSs (Faisal et al., 2019; Guilbaud et al., 2008; Montazeri, Himelbloom, et al., 2013). PCS is used either by dipping the seafood product in a diluted PCS solution or by atomizing it and spraying the sample in a closed chamber.…”
Section: Mild Processing Methods For Seafoodmentioning
confidence: 99%
“…Smoke condensates are usually obtained from wood smoke produced by smoldering wood chips or sawdust followed by refining and rinsing steps to remove unwanted compounds (Guillén et al., 2000; Montazeri, Oliveira, et al., 2013). Despite the filtering, the active antimicrobial compounds are still the same and research has shown an inhibiting effect of several types of PCSs (Faisal et al., 2019; Guilbaud et al., 2008; Montazeri, Himelbloom, et al., 2013). PCS is used either by dipping the seafood product in a diluted PCS solution or by atomizing it and spraying the sample in a closed chamber.…”
Section: Mild Processing Methods For Seafoodmentioning
confidence: 99%
“…Pyrolysis temperature plays an important role in the composition of the liquid smoke [17], which is one of the parameters for determining the quality of the liquid smoke produced. Liquid smoke has several components, including phenol, acetic acid, ethanol, cyclopentanone, and propionic acid [6]. Tables 1-3 present the various chemical compounds obtained from rice husk pyrolysis at 300°C-400°C.…”
Section: Gc-ms Testmentioning
confidence: 99%
“…Making liquid smoke from rice husks provides many benefits, particularly because it reduces the size of the husk waste pile. Liquid smoke from various biomasses, including palm kernel shell [3,4], durian husk [5,6], rice husk [7,8], bamboo [9], oil palm empty bunches [10,11], sawdust [12], and cacao bark [13], has been used as a natural preservative for various foodstuffs. Moreover, liquid smoke can also be used in agriculture for biological pest control, for example, to anticipate anthracnose in chilies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid smoke is a product of the process of breaking wood structures with high temperature. 4 Several ingredients in Indonesia that can be used to produce liquid smoke include rice husks, 5 coconut shells, 6 7 durian, 8 lamtoro, corn comb, 9 bamboo, 10 and cocoa bean skin. 11 Of these various types of materials, rice husks have been shown to have the potential to treat various diseases, including periodontitis, 12 oral ulcer, 13 14 15 16 diabetes, 17 18 and burn.…”
Section: Introductionmentioning
confidence: 99%